From Culturazing Nature to Naturalizing Culture: The Differing Function of Animal Imagery in Defining Bodies from Homer’s Odysseus to Margaret Atwood’s The Penelopiad - Tuğlu, Begüm (European Journal of Social Science Education and Research, 2016)
Feminist authors have long been trying to alter the patriarchal structure of the Western society through different aspects. One of these aspects, if not the strongest, is the struggle to overcome centuries long dominance of male authors who have created a masculine history, culture and literature. As recent works of women authors reveal, the strongest possibility of actually achieving an equalitarian society lies beneath the chance of rewriting the history of Western literature. Since the history of Western literature relies on dichotomies that are reminiscences of modernity, the solution to overcome the inequality between the two sexes seems to be to rewrite the primary sources that have influenced the cultural heritage of literature itself. The most dominant dichotomies that shape this literary heritage are represented through the bonds between the concepts of women/man and nature/culture. As one of the most influential epics that depict these dichotomies, Homer’s Odysseus reveals how poetry strengthens the authority of the male voice. In order to define the ideal "man", Homer uses a wide scope of animal imagery while forming the identities of male characters. Margaret Atwood, on the other hand, is not contended with Homer’s poem in that it never narrates the story from the side of women. As a revisionist mythmaker, Atwood takes the famous story of Odysseus, yet this time presents it from the perspective of Penelope, simultaneously playing on the animal imagery. Within this frame, I intend to explore in this paper how the animal imagery in Homer’s most renowned Odysseus functions as a reinforcing tool in the creation of masculine identities and how Margaret Atwood’s The Penelopiad defies this formation of identities with the aim of narrating the story from the unheard side, that of the women who are eminently present yet never heard.